Does keto make the difference? A comprehensive review of its impact on physical activity, cognitive function and hormonal balance. - Papież, Łukasz Stanisław; Dołęga, Julia; Zabawa, Bartłomiej; Krzykawski, Karol; Maciejczyk, Tomasz; Sieńko, Antoni; Hudzińska, Patrycja; Sadowski, Jakub; Mól, Piotr; Łabuś, Małgorzata (Quality in Sport, 2024)
Introduction: The ketogenic diet, characterized by high fat and low carbohydrate intake, has become increasingly popular among athletes and fitness enthusiasts due to its potential for supporting weight loss and enhancing metabolic health. This study aims to analyze the impact of the keto diet on physical and cognitive performance, as well as to understand the mechanisms and challenges associated with its use. Materials and methods: A systematic review of available studies was conducted through extensive searches in databases such as PubMed, NCBI, and Google Scholar. State of knowledge: The ketogenic diet can be beneficial in endurance sports by improving fat utilization as an energy source and increasing energy stability, but its impact on aerobic capacity and time to exhaustion varies. In strength sports that require intense effort, carbohydrate restriction can negatively affect strength and muscle mass development, as glycogen is a key energy source in such activities. The ketogenic diet does not provide full benefits in high-intensity sports, such as sprints or team sports, due to limited glycogen availability. The ketogenic diet can improve body composition and metabolic efficiency in athletes, but its impact on performance depends on individual responses, and the adaptation process may involve challenges such as "keto flu." Ketogenic diet may positively impact mental health by reducing symptoms of anxiety and depression. Additionally, it may enhance sleep quality, particularly by supporting deep sleep, and potentially increase testosterone production. Conclusions: The ketogenic diet can benefit endurance sports by improving fat oxidation and sustaining energy levels, though its effectiveness in high-intensity, glycogen-dependent activities is less certain. Strategies like TKD or CKD, along with performance monitoring, can help athletes optimize results.